Harnessing the Diversity of Ideas for Competitive Advantage. Issue 3 (12th November 2019) - Morgan, Johnny D.
ABSTRACT: The engineering community has made significant advances in traditional diversity measures in the last 50 years, but because the world has become more complex, the engineering community needs to embrace new ideas that are outside the realm of traditional engineering disciplines. This paper identifies that individuals are the sources of new ideas, but it is organizations that transform these ideas into value‐delivered innovations. It examines the relationship of maximizing information diversity to promote idea discovery while minimizing work force diversity to promote the sharing and acceptance of these ideas. It then discusses the concept of inclusion as a necessary team skill for organizations to deliver these ideas as innovations. This paper concludes by identifying systems engineering behaviors that create a diverse environment for idea discovery and an inclusive team environment that overcomes challenges and transitions ideas into delivered innovations, thus providing a competitive advantage.